(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2020)
AIMS AND OBJECTIVES: Comparison between Early versus Delayed Laparoscopic Cholecystectomy in 50 patients of Acute Calculus Cholecystitis MATERIALS AND METHODS: A systematic review was performed by randomized clinical trials of early laparoscopic cholecystectomy (performed within 48 hours of onset of symptoms) versus delayed laparoscopic cholecystectomy (performed at least 6 weeks after symptoms settled) for acute cholecystitis. 25 Cases each in early group and delayed group were selected at VSGH from January,2018 to December,2018 according to their time of presentation of their first symptom. Parameters were recorded intraoperative complications, timing of surgery, postoperative morbidity, days of hospital stay and conversion to open surgery. RESULTS:Out of 50 patients, the overall morbidity and complications are less in Early laparoscopic cholecystectomy (ELC) compared to Delayed laparoscopic cholecystectomy (DLC). Mean operative time is less in ELC (70 minutes) and DLC (82 minutes).Mean number of hospital stay is less in ELC (6 days) whereas DLC (8 days). Overall hospitalization stay, morbidity, ICU admissions are less in Early laparoscopic cholecystectomy.CONCLUSON:Early laparoscopic cholecystectomy (within 48 hours) from start of symptoms of acute calculous cholecystitis: is safe, feasible and shortens the duration of hospital stay.